Low-Power Analog Techniques, Sensors for Mobile Devices, and Energy Efficient Amplifiers Advances in Analog Circuit Design 2018 - Makinwa, Kofi A. A.; Baschirotto, Andrea; Harpe, Pieter (Springer International Publishing : Imprint: Springer, 2019)
This book is based on the 18 invited tutorials presented during the 27th workshop on Advances in Analog Circuit Design. Expert designers from both industry and academia present readers with information about a variety of topics at the frontiers of analog circuit design, including the design of analog circuits in power-constrained applications, CMOS-compatible sensors for mobile devices and energy-efficient amplifiers and drivers. For anyone involved in the design of analog circuits, this book will serve as a valuable guide to the current state-of-the-art. Provides a state-of-the-art reference in analog circuit design, written by experts from industry and academia; Presents material in a tutorial-based format; Covers the design of analog circuits in power-constrained applications, CMOS-compatible sensors for mobile devices and energy-efficient amplifiers and drivers.